Hubungan Pemberian ASI Eksklusif dengan Status Gizi Pada Balita Usia 1-2 Tahun di Wilayah Kerja Puskesmas Tekung Kecamatan Tekung Kabupaten Lumajang - Leny Widya Eka Fayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study plans to inspect the connection between sound status and particular breastfeeding (EBF) among kids matured 1-2 at the Tekung Social class Prosperity Center, Lumajang System. Using a cross-sectional survey design and an analytical approach, the study's population consisted of all mothers and infants aged six to twelve months in the Tekung Community Health Center's working area, with a sample size of forty infants. Mothers with children ranging in age from one to two were included as long as they were willing to participate as respondents. Random sampling was used as the sampling method. The questionnaires and anthropometric observations were used to collect the data using univariate and bivariate techniques. By demonstrating a significant relationship (p-esteem = 0.01) between restrictive breastfeeding and an individual's healthful status, the study demonstrated the significance of selective breastfeeding for the nutrition of babies. These results are consistent with past assessment and stress the multifaceted design of the association between healthy status and specific breastfeeding